Relationship between Mediterranean diet, physical activity and emotional intelligence in Spanish undergraduates - Daniel Sanz-Martín; Félix Zurita-Ortega; Javier Cachón-Zagalaz; Eduardo Melguizo-Ibáñez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Levels of adherence to the Mediterranean diet in Spanish university students need to be verified. It is necessary to go deeper into what these are and what factors determine them. This is useful to design effective diet promotion proposals in this population. The objectives are: 1) To classify Spanish university students of Education Degrees according to their levels of Mediterranean diet, physical activity and emotional intelligence; 2) To analyse the influence of physical activity and emotional intelligence as determinants of Mediterranean diet according to lifestyle profiles. A cross-sectional study was designed with the participation of a representative sample of university students of education degrees. Participants ranged in age from 18 to 43 years (20.84±2.90). Men represented 30.2% of the sample (n=125) and women 69.8% (n=289). An online questionnaire was administered comprising the following: PREDIMED, IPAQ-SF and TMMS-24. The regression model obtained for the whole sample was: Mediterranean diet= 2.536+0.001*physical activity+0.029*emotional intelligence. The two-stage cluster classification (Ward and k-means) was validated with the MANOVA test (Pillai trace: F (6, 820) = 159.101; p ≤ 0.001; f = 1.00). It is concluded that 8% of university students' adherence to the Mediterranean diet is predicted by moderate-vigorous physical activity and emotional intelligence. Adherence to the diet is positively related to physical activity and emotional intelligence.